The abaI/abaR Quorum Sensing System Effects on Pathogenicity in Acinetobacter baumannii - Sun, Xiaoyu; Ni, Zhaohui; Tang, Jie; Ding, Yue; Wang, Xinlei; Li, Fan (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is a Gram-negative pathogen that has emerged as one of the most troublesome pathogens for health care institutions globally. Bacterial quorum sensing (QS) is a process of cell-to-cell communication that relies on the production, secretion and detection of autoinducer (AI) signals to share information about cell density and regulate gene expression accordingly. The molecular and genetic basis of Acinetobacter baumannii virulence remains poorly understood. Therefore, the contribution of the abaI/abaR quorum sensing system to growth characteristics, morphology, biofilm formation, resistance, motility and virulence of Acinetobacter baumannii was studied in detail. RNA-seq analysis indicated that genes involved in various aspects of energy production and conversion, Valine, leucine and isoleucine degradation and lipid transport and metabolism are associated with bacterial pathogenicity. Our work provides a new insight into abaI/abaR quorum sensing system effects pathogenicity in A. baumannii. We propose that targeting the AHL synthase enzyme abaI could provide an effective strategy for attenuating virulence. On the contrary, interdicting the autoinducer synthase–receptor abaR elicits unpredictable consequences, which may lead to enhanced bacterial virulence.